Unique Poetry Of Azam Uktam - Kurbanova Mukaddas Omonovna; Dilfuza Uktamovna Khusenova (Research Parks Publishers, 2021)
The article defines the work of the poet Azam Uktam and tells about the unique and rare artistic phenomenon of this creator